2019
DOI: 10.1038/s41598-019-48064-w
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer Testis Antigen Promotes Triple Negative Breast Cancer Metastasis and is Traceable in the Circulating Extracellular Vesicles

Abstract: Triple negative breast cancer (TNBC) has poor survival, exhibits rapid metastases, lacks targeted therapies and reliable prognostic markers. Here, we examined metastasis promoting role of cancer testis antigen SPANXB1 in TNBC and its utility as a therapeutic target and prognostic biomarker. Expression pattern of SPANXB1 was determined using matched primary cancer, lymph node metastatic tissues and circulating small extracellular vesicles (sEVs). cDNA microarray ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…RAC1 regulates the activation of vinculin, a well-characterized focal adhesion protein involved in many steps of cell migration 46,48 . In triple negative breast cancer cells reduction of tumorigenic phenotypes is accompanied by reduced expression of RAC1, alpha-actinin, vinculin and FAK 65 and silencing of vinculin reduces cell viability www.nature.com/scientificreports/ and decreases tumor volume in animal models 66 . The decrease in vinculin assembly observed in MDA-MB-231 cells overexpressing V1G1 is associated to a decrease in RAC1 protein amount (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RAC1 regulates the activation of vinculin, a well-characterized focal adhesion protein involved in many steps of cell migration 46,48 . In triple negative breast cancer cells reduction of tumorigenic phenotypes is accompanied by reduced expression of RAC1, alpha-actinin, vinculin and FAK 65 and silencing of vinculin reduces cell viability www.nature.com/scientificreports/ and decreases tumor volume in animal models 66 . The decrease in vinculin assembly observed in MDA-MB-231 cells overexpressing V1G1 is associated to a decrease in RAC1 protein amount (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Testis-specific lactate dehydrogenase C4 was upregulated in serumal exosomes from breast cancer patients [130]. CT antigen SPANXB1 was exclusively expressed in circulating small EVs and promoted the metastasis of triple-negative breast cancer [131]. In other words, expression of CT antigens correlates with tumour progression, and tumour-expressed CT antigens can be combined with exosomes for antigenic presentation.…”
Section: Exosomal Expression Linked To Cancer Progression: Oncogenic mentioning
confidence: 99%
“…For example, SPANXB1 expression was associated with increased migration and invasion abilities. In addition, its mRNA and protein levels were negatively correlated with the metastasis suppressor gene SH3GL2 [31].…”
Section: Aberrant Antigen Expressionmentioning
confidence: 99%
“…Similarly, gene promoter hypermethylation has been proposed as a mechanism able to silence neo-antigen expression [27]. In TNBC, specifically, different studies have identified the upregulation of NY-ESO-1, MAGE-1, WT1, and SPANXB1 [29][30][31]. Thus, aberrant CTA expression in TNBC has become a therapeutic opportunity.…”
Section: Aberrant Antigen Expressionmentioning
confidence: 99%